2014
DOI: 10.3389/fnhum.2014.00301
|View full text |Cite
|
Sign up to set email alerts
|

Less Effort, Better Results: How Does Music Act on Prefrontal Cortex in Older Adults during Verbal Encoding? An fNIRS Study

Abstract: Several neuroimaging studies of cognitive aging revealed deficits in episodic memory abilities as a result of prefrontal cortex (PFC) limitations. Improving episodic memory performance despite PFC deficits is thus a critical issue in aging research. Listening to music stimulates cognitive performance in several non-purely musical activities (e.g., language and memory). Thus, music could represent a rich and helpful source during verbal encoding and therefore help subsequent retrieval. Furthermore, such benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 109 publications
(203 reference statements)
4
63
2
1
Order By: Relevance
“…Previous fNIRS studies have investigated DLPFC contribution to several processes cognitive, such as word-encoding in a memory task (Ferreri et al, 2014), inhibitory control in drug users (Roberts & Montgomery, 2015), dual motor and cognitive task-performance (Mandrick et al, 2013). Relevant to the current results, two studies targeted hemodynamic responses in DLPFC in effortful tasks, specifically testing the effect of varying mental load in a working memory task (Molteni et al, 2012), and comparing laboratory measures of load (executive function task) with real-life effort (operating a flight-simulator Causse et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous fNIRS studies have investigated DLPFC contribution to several processes cognitive, such as word-encoding in a memory task (Ferreri et al, 2014), inhibitory control in drug users (Roberts & Montgomery, 2015), dual motor and cognitive task-performance (Mandrick et al, 2013). Relevant to the current results, two studies targeted hemodynamic responses in DLPFC in effortful tasks, specifically testing the effect of varying mental load in a working memory task (Molteni et al, 2012), and comparing laboratory measures of load (executive function task) with real-life effort (operating a flight-simulator Causse et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…After data collection, one participant was excluded from further analysis due to technical failure. Sample size was determined based on previous studies using fNIRS to investigate cognitive function (Causse, Chua, Peysakhovich, Del Campo, & Matton, 2017; Ferreri et al, 2014; Nakahachi et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…However, this was from examining task-orientated changes, where the general cerebral hemodynamic perturbations could induce responses for both groups. Ferreri et al (2014) suggested that the greatest cerebral hemodynamic changes happen from task orientated protocols, and thus we used the ''Where's Wally'' paradigm for this function. The literature further bolsters that it can be more than generic changes as Akın and Bilensoy (2006) reported HHb increases within protocols that induce metabolic perturbations.…”
Section: Between-group Differences In Fnirs Outcome Measuresmentioning
confidence: 99%
“…Los resultados comportamentales indicaron que la música de fondo facilitó la codificación y aumentó el recuerdo de palabras, mientras que los datos de neuroimagen mostraron una menor activación general de la corteza prefrontal durante la tarea que tenía a la música como contexto, lo que indicaría una menor exigencia neurocognitiva para codificar y evocar material verbal. Resultados similares fueron hallados en adultos mayores (Bottiroli, Rosi, Russo, Vecchi, & Cavallini, 2014;Ferreri, Bigand, Perrey, Muthalib, Bard, & Bugaiska, 2014) y niños (Hallam, Price, & Katsarou, 2002).…”
Section: Resultsunclassified